Wanted: toddler's personal assistant eaudiobook How nannying for the 1% taught me about the myths of equality, motherhood, and upward mobility in america. - Kiser, Stephanie (Tantor Media, 2024)
What are the lives of America's richest families really like? Their nannies see it all . . . When Stephanie Kiser moves to New York City after college to pursue a career in writing, she quickly learns that her entry-level salary won't cover the cost of living. But there is one in-demand job that pays enough to allow Stephanie to stay in the city: nannying for the 1%. Desperate to escape the poverty of her own childhood, Stephanie falls into a job that hijacks her life for the next seven years: a glorified personal assistant to toddlers on Manhattan's Upper East Side. At first, nannying seems like the perfect solution—the high pay covers Stephanie's bills, and she's surprised by how attached she becomes to the kids she cares for, even as she gasps over Prada baby onesies and preschools that cost more than her college tuition. But the grueling twelve-hour days leave her little time to see her friends, date, or pursue any creative projects that might lead to a more prestigious career. The allure of the seemingly-glamorous job begins to dull as Stephanie comes to understand more about what really happens behind the closed doors of million-dollar Park Avenue apartments—and that money doesn't guarantee happiness. Soon she will have to decide whether to stay with the children she's grown to love, or if there's something better out there.